Long-term performance of full-depth precast concrete (FDPC) deck panels. (1st October 2021) - Shahrokhinasab, Esmail; Garber, David
Highlights: The three joints with the best overall behavior are the UHPC with straight bar, longitudinal post-tensioned, and conventional concrete with hooped bar details. FDPC deck panels have the shortest average estimated service life in cold climate zones. There was no significant difference in performance between bridges using FDPC deck panels for new construction compared with those using them for rehabilitation projects. Bridges with wearing surfaces including micro silica concrete, polyester polymer, and silica fume concrete have longer estimated service lives. Machine learning model for bridge degradation is more reliable than linear regression model for bridge deterioration as it considers the effect of multiple variable at a time. Abstract: Full-depth precast concrete (FDPC) deck panels are becoming more popular recently as they can accelerate construction. However, there are still concerns about durability, proper connections, and long-term performance that have limited their widespread use in the U.S. Most studies on FDPC deck panels have been on their short-term structural performance and joint behavior; there is minimal published work addressing the long-term performance of these structures. A survey was developed and sent out to all state departments of transportation (DOTs) for the work described in this paper. The information gathered from this survey included: a list of bridges using FDPC deck panels (with details about projects), cost, observed performance, experience with panels, and types of joints used. The FDPC Deck Panel Database was developed based on the collected information from this survey and combined with information from the National Bridge Inventory (NBI) database. The performance of bridges in the database was evaluated based on the deck deterioration rate and estimated service life according to simple linear regression and a deep learning models provided by Long-Term Bridge Performance (LTBP) InfoBridge. The result of this effort was identification of the performance of bridges with FDPC deck panels under different conditions. Joint type, traffic impact category (i.e., time construction impacts traffic), climate zone, wearing surface type, and traffic were found to impact the behavior of bridges with FDPC deck panels. Construction type (new construction versus rehabilitation) did not influence the behavior of these bridges.